A Mongol Moment in Islamic Jurisprudence: Did Ibn Taymiyya Excommunicate Errant Muslim Rulers for Failing to Implement Sharia? - Surjányi, Dávid (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
Many Islamic fundamentalists today retrace their ‘law of war’ back to a medieval jurist called Ibn Taymiyya. One of the most controversial elements in the mufti’s legacy was when he issued the so-called Mardin fatwa against the Mongol leaders of the Ilkhanate. Ibn Taymiyya declares these leaders kafir (act of takfir) for not implementing Sharia law in the Ilkhanate despite their conversion to Sunni Islam. The question of this paper is whether this fatwa means that Ibn Taymiyya advocated for rebellion against wayward Muslim leaders or not. This paper does what only a few works on Ibn Taymiyya ventured so far: not only to shed light on the historical context in which the legal instrument of the Mardin fatwa was issued but also to concurrently elaborate on Ibn Taymiyya’s stance on Muslim authority. Thus, the research establishes that taking into account his other works as well, it is clear that the mufti did not wish to initiate an internal jihad against Muslim leaders, as he did not even regard the Ilkhans as Muslims. Therefore, what he did is to call for the basic form of military jihad against unbelievers. While vast research concentrates on the mufti’s longstanding influence on fundamentalists, our present comparative analysis also examines how the Mardin fatwa has been invoked by modern Islamists and jihadists to justify violent actions against their national leaders, based on a particular interpretation of Sharia derived from a medieval jurist whose formulation was sufficiently ambiguous to arguably permit such usage. Ideally, this contributes to the library worth of research regarding the mufti inasmuch as it sheds new light on the real impact Ibn Taymiyya has had on the development of Islamic law of war (Fiqh al-Jihad).